Conception d’un outil d’analyse du comportement de systèmes biologiques - Lorène Prost; Christophe Lecomte; Jean Marc Meynard; Marianne Cerf (Activités)
New cultivars have always been a key element in the development of cropping systems. The assessment of new cultivar performance in a diverse range of environments (soil, climate, production methods) is a key issue for the actors along the chain which links breeders to growers and food suppliers. As agronomists and ergonomists, we worked together to design a tool aimed at supporting these actors in assessing cultivar performance in order to link three aspects of the design process: (i) the crystallisation in the tool of an activity model, (ii) the flexibility of the tool, (iii) the joint development of the tool and the activity. To produce specifications based on these aspects, we analysed respectively (i) the invariants of the activity system of cultivar assessment, (ii) the diversity of actions performed by actors involved in cultivar assessment, (iii) the contradictions which arise within the activity system. Our analysis calls on existing historical studies but is based mainly on interviews with 21 people involved in cultivar assessment and gave us an insight into the actions of assessment activity. This analysis enables us to point out that the network of field trials is a key tool for the activity of cultivar assessment and to study how actors take advantage of the vagueness of the various tools to transform them into instruments. It also shows that, historically, the object of the activity has been built around assessing the stability of cultivar performance and that stability still gives direction to the actions undertaken by actors today. Eleven different actions for evaluating cultivars were identified. Our analysis highlights the contradictions which emerge today within the object of the activity system due to the new issues that actors have to face. It led us to define specifications for a prototype tool which is flexible enough to adapt to the diversity of actions and which could be used to enable actors to overcome some of the contradictions identified.